2012
DOI: 10.1016/j.ijscr.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernia of the urinary bladder following internal hemipelvectomy

Abstract: Hemipelvectomies are extensive, anatomically disruptive operations, with significant detriment to the psychosomatic well being of the patients. We presented the only reported case of incisional hernia of the urinary bladder following internal hemipelvectomy and our reconstructive method of choice. We believe that, in the case of our patient, if a mesh had been used to reconstruct the primary defect during the initial surgery, this complication could have been prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Incisional hernia secondary to external/internal hemipelvectomy has been reported. [9][10][11][12][13] Only 2 cases of bladder hernia secondary to type 3 internal hemipelvectomy have been reported. 12,13 One case was severe, could not be repaired surgically, and necessitated intermittent self-catheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…Incisional hernia secondary to external/internal hemipelvectomy has been reported. [9][10][11][12][13] Only 2 cases of bladder hernia secondary to type 3 internal hemipelvectomy have been reported. 12,13 One case was severe, could not be repaired surgically, and necessitated intermittent self-catheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that hernias tend to be underreported because they are often subclinical compared with more serious complications following internal hemipelvectomy. 22 In the 2 current patients, neither avascular necrosis nor hernia were seen in long-tem follow-up. However, 1 patient developed lymphedema after radiation but had no evidence of lymphedema in the 2-month period from surgery until radiation began, suggesting that the lymphedema was associated with radiation to the operative area.…”
Section: Surgical Outcomesmentioning
confidence: 71%
“…9,10 Abdominal wall complications are rarely reported after internal hemipelvectomy. 8 In standard anterior hemipelvectomies, there is enough muscular mass in the adductor compartment to allow for a solid repair of the lower abdominal wall and inferior (adductor or femoral) hernias are uncommon. In the case presented herein, the extent of resection included the adductor compartment resulting in a weaker-than-desired repair of the pelvic floor, despite the use of polypropylene mesh.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Few cases of incisional hernia have been reported after internal hemipelvectomy probably because most cases are asymptomatic or overshadowed by more serious complications. 8 A case of late complex hypogastric and femoral incisional hernia after extended hemipelvectomy for recurrent osteosarcoma treated with distal abdominal wall fixation into a free fibula flap is reported. To the best of the authors' knowledge, no similar technique has been described previously in the English literature.…”
Section: Introductionmentioning
confidence: 99%